2008
DOI: 10.1121/1.2824018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moderate cochlear hearing loss on the ability to benefit from temporal fine structure information in speech

Abstract: Speech reception thresholds (SRTs) were measured with a competing talker background for signals processed to contain variable amounts of temporal fine structure (TFS) information, using nine normal-hearing and nine hearing-impaired subjects. Signals (speech and background talker) were bandpass filtered into channels. Channel signals for channel numbers above a "cut-off channel" (CO) were vocoded to remove TFS information, while channel signals for channel numbers of CO and below were left unprocessed. Signals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
194
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(211 citation statements)
references
References 67 publications
13
194
1
Order By: Relevance
“…The present findings are thus in line with the increasing evidence for an important and independent role of TFS processing in hearing (e.g., Lacher-Fougère and Demany, 2005;Lorenzi et al, 2006;Hopkins et al, 2008;Strelcyk and Dau, 2009). However, this remains a controversial issue.…”
Section: B Correlations Between the Auditory Profile Measuressupporting
confidence: 80%
“…The present findings are thus in line with the increasing evidence for an important and independent role of TFS processing in hearing (e.g., Lacher-Fougère and Demany, 2005;Lorenzi et al, 2006;Hopkins et al, 2008;Strelcyk and Dau, 2009). However, this remains a controversial issue.…”
Section: B Correlations Between the Auditory Profile Measuressupporting
confidence: 80%
“…Enhanced envelope coding produces a "relative" fine-structure coding deficit Recent perceptual studies suggest that hearingimpaired listeners have reduced ability to use finestructure cues for both speech and pitch perception (Buss et al 2004;Lorenzi et al 2006;Hopkins and Moore 2007;Hopkins et al 2008); however, the physiological correlates of this fine-structure deficit continue to be debated (Moore and Carlyon 2005;Moore 2008). Although the fundamental ability of AN fibers to phase lock to fine structure was not degraded following SNHL (Fig.…”
Section: Physiological Sources Of Enhanced Envelope Codingmentioning
confidence: 99%
“…In the experiment of Hopkins et al (2008), listeners with moderate cochlear hearing loss were also tested. The mean results are shown by the filled circles in Figure 3.…”
Section: Speech Perception Studiesmentioning
confidence: 99%
“…The reasons for the individual differences are not at present clear. Hopkins et al (2008) reported that the benefit gained from the addition of TFS information was not correlated with the average audiometric threshold over the range 250 to 4,000 Hz.…”
Section: Speech Perception Studiesmentioning
confidence: 99%